Lab on a chip sensor for rapid detection and antibiotic resistance determination of Staphylococcus aureus. Issue 6 (26th January 2016) - Abeyrathne, Chathurika D.; Huynh, Duc H.; Mcintire, Thomas W.; Nguyen, Thanh C.; Nasr, Babak; Zantomio, Daniela; Chana, Gursharan; Abbott, Iain; Choong, Peter; Catton, Mike; Skafidas, Efstratios
Abstract : Silicon dioxide passivated, interdigitated electrode sensor for rapid detection and antibiotic resistance determination of S. aureus . Abstract : The Gram-positive bacterium, Staphylococcus aureus ( S. aureus ), is a major pathogen responsible for a variety of infectious diseases ranging from cellulitis to more serious conditions such as septic arthritis and septicaemia. Timely treatment with appropriate antibiotic therapy is essential to ensure clinical defervescence and to prevent further complications such as infective endocarditis or organ impairment due to septic shock. To date, initial antibiotic choice is empirical, using a "best guess" of likely organism and sensitivity- an approach adopted due to the lack of rapid identification methods for bacteria. Current culture based methods take up to 5 days to identify the causative bacterial pathogen and its antibiotic sensitivity. This paper provides proof of concept for a biosensor, based on interdigitated electrodes, to detect the presence of S. aureus and ascertain its sensitivity to flucloxacillin rapidly (within 2 hours) in a cost effective manner. The proposed method is label-free and uses non-faradic measurements. This is the first study to successfully employ interdigitated electrodes for the rapid detection of antibiotic resistance. The method described has important potential outcomes of faster definitive antibiotic treatment and more rapid clinical response to treatment.